The concept and essence of the phenomenon of interaction between the State and religious confessions in the conceptual dimension - Аймухамбетов, Тимур (Eurasian Journal of Religious Studies, 2017)
In this article the authors have done work on the analysis of concepts and the essence of interaction between the state and religious faiths in the conceptual dimension. One of the problems associated with the interaction of the state and religion and religious organizations of modern states is the concept and essence of this phenomenon. Despite the secularization of state and religious institutions, "the religious factor influences the economy, politics, and the state itself and society, respectively – interethnic relations, the family, into the cultural field through the activities of believing individuals, groups, organizations in these areas." Thus, there is a certain reproduction of religious relations on the background of social relations. For a deeper analysis of this topic, it is necessary to classify in more detail the concepts and essence of this direction.